2014
DOI: 10.1063/1.4861598
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the surface conditioning of trapezoidally shaped silicon nanowires by (3-aminopropyl)triethoxysilane

Abstract: We report on the electrical performance of silane-treated silicon nanowires configured as n+ – p – n+ field effect transistors. The functionalization of the silicon oxide shell with (3-aminopropyl)triethoxysilane controls the formation of the conduction channel in the trapezoidal cross-section nanowires. By carefully adjusting the surface conditioning protocol, robust electrical characteristics were achieved in terms of device-to-device reproducibility for the studied silicon nanowire transistors: the standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…So, this alkoxide can form a silicon oxide three-dimensional network in which there is the possibility of bonding through the Si–OH and the NH 2 end groups. It can be used in the production of plastic reinforced with fiber in order to improve its mechanical strength, compressive strength, resistance to moist environments, as well as the wettability and dispersion of polymer fillers [ 24 , 25 ]. In addition, it is often used as a coupling agent for bonding organic molecules to hydroxylated silicon oxide or metal oxide substrates, due to the presence of the terminal amino group on the propyl chain, through reaction with glutaraldehyde, a bifunctional aldehyde.…”
Section: Introductionmentioning
confidence: 99%
“…So, this alkoxide can form a silicon oxide three-dimensional network in which there is the possibility of bonding through the Si–OH and the NH 2 end groups. It can be used in the production of plastic reinforced with fiber in order to improve its mechanical strength, compressive strength, resistance to moist environments, as well as the wettability and dispersion of polymer fillers [ 24 , 25 ]. In addition, it is often used as a coupling agent for bonding organic molecules to hydroxylated silicon oxide or metal oxide substrates, due to the presence of the terminal amino group on the propyl chain, through reaction with glutaraldehyde, a bifunctional aldehyde.…”
Section: Introductionmentioning
confidence: 99%
“…It is a catalyst in the platinum by the chloroform and alkene with the active group and then obtained by alcoholysis. They can also be used in surface conditioning to obtain devices with reproducible electrical characteristics for molecular detection applications, functionalized as reference devices for biological chemical sensors [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…This roughness can cause additional surface forces to suppress the contraction of the threephase contact line [23,26]. Third, studies have shown that the APTES film is not well organized and its struc-ture is not compact [25,27,28]. Some authors reported that water molecules can penetrate even into a dense organic layer if the hydrophobic chains are too short, which can induce deformation of the organic layer and result in additional force on the sample [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17] A plethora of techniques were proposed for the reliable fabrication of Si nanostructures and SiNWs. [18][19][20][21][22][23][24] Yet, most of these methods require specialized equipment and involve highly sensitive procedures for mass production. In contrast, metal-assisted chemical etching (MACE) associated with a nanostructured continuous catalyst profits from the simplicity of the electroless etching process while allowing for the control of various parameters: morphology (solid or porous), diameter, length, and to a certain extent, crystallographic orientation.…”
Section: Introductionmentioning
confidence: 99%